IMPROVING THE USE OF OPEN-PIT OIL FIELD (American Journal of Technology and Applied Sciences, 2024)
The only factor explaining the difference between these two straight sections is that during the period characteristic of each of them, the density of the well pattern was compacted. As is known, one of the main parameters that allows us to evaluate the effectiveness of hydrodynamic methods is the amount of recoverable reserves and the final oil recovery factor.